AI-Aided Control of a Power Converter in Wind Energy Conversion System - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2020)
Over the last decades, to adopt high penetration of renewable energy sources (RESs) in electrical energy systems, distributed energy resources (DERs) have become prominent. Due to easy attainability status of small wind turbines (WTs), wind energy conversion systems (WECSs) are feasible applications for small customers, especially in windy areas. The next decade is likely to witness a considerable rise in DERs. In this context, WECSs are preferred broadly, thus harvesting wind energy into electrical energy effectively is a substantial issue. WTs can be got involved in the grid-connected or autonomous mode with a variety of topologies. In this paper, we examine to control of DC-DC boost converter of a WECS with the help of artificial intelligence (AI)aided PI controller. Regarding the proposed method, artificial neural networks (ANNs) as a subset of AI are utilized. To test and ensure the applicability of the proposed control method, a small WECS with a permanent magnet synchronous generator (PMSG) connected a DC bus was implemented in MATLAB/Simulink environment. The results present that dynamic response and less complexity with a high accuracy rate have been obtained under study. © 2020 IEEE.
Keywords: Artificial Intelligence; Artificial Neural Network; Power Converters; Wind Energy Conversion System